2018
DOI: 10.1097/pq9.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Time to Pain Medication Administration for Pediatric Patients with Long Bone Fractures in the Emergency Department

Abstract: Introduction: Pain management is a critical aspect of effective long bone fracture treatment. Pediatric patients frequently report suboptimal pain management, which is an area of growing public concern. The purpose of this quality improvement project was to develop a protocol with the goal to administer pain medication to children presenting with suspected long bone fractures ≤47 minutes of emergency department arrival. Methods: A multidisciplinary team developed a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Despite this, we were able to find significant differences in the probability of receiving analgesia when the patient is attended by a traumatologist. The work by Schuman et al 17 showed a reduction in the time of analgesia administration in pediatric patients in the ED after the implementation of a standardized pain management protocol for patients presenting with musculoskeletal pain under a nurse-initiated order. In it, it was evidenced that the median time of medication administration decreased from 71.5 minutes before the protocol to 26 minutes after the implementation of the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, we were able to find significant differences in the probability of receiving analgesia when the patient is attended by a traumatologist. The work by Schuman et al 17 showed a reduction in the time of analgesia administration in pediatric patients in the ED after the implementation of a standardized pain management protocol for patients presenting with musculoskeletal pain under a nurse-initiated order. In it, it was evidenced that the median time of medication administration decreased from 71.5 minutes before the protocol to 26 minutes after the implementation of the protocol.…”
Section: Discussionmentioning
confidence: 99%